Mental Health Advocacy in The Gambia, West Africa - Njai Safiya; Thorson-Olesen Stephanie (Mental Health: Global Challenges Journal, 2023)
Introduction: To promote mental health globally, including low-and middle-income countries, research and advocacy are essential. The Republic of The Gambia is one of the smallest countries in the world and is the focus of this research.